A tradução do personagem Winston Smith, de Nineteen Eighty-Four, para o cinema - Silva Júnior, Henrique Gomes da (2019)
The novel Nineteen Eighty-Four, by George Orwell became world famous at the time of its first publication for approaching significant themes to the context in which it was placed, like the war, totalitarian governments and the threat of the end of private freedom. The work cited is pointed by the critics as a pessimistic representation of the future first half 20th century society, by representing the main character, Winston Smith, trapped in a scenario of control and oppression. The novel is considered a classic among the dystopian works and it was adapted twice for the cinema, the first was produced in 1956 and the other in 1984 with homonymous title and directed by Michael Radford. The objective of this research is to analyze what translation resources were used to adapt the main character to the cinematographic version aforesaid. We start with the idea that the movie production choose to simplify the construction of the protagonist, stressing the pessimism of the dystopian genre and suppressing some parts of the novel that show a partial optimistic development of the character. As theoretical support we used the studies by Cartmell (2012) on general aspects of adaptation and Catrysse (1995) that considers the process of adaptation as translation. We also applied theories on adaptation of literary works to the cinema from Hutcheon (2004) as well as researches on fiction characters from Cândido (1014), Bakhtin (2010) and Brait (2017). Finally we used the studies of Rodden (2007), Baccolini and Moylan (2003) on literary aspects in general and the works of Cousins (2013), Bordwell and Thompson (2008) and others about the elements of movie narrative composition. The preview results showed that the adaptation translated to the big screen some aspects that reinforce the projection of a dehumanized character, oppressed by the environment where he lived through showing violent scenes, photography with neuter colors, visual metaphors and etc. It was also possible to observe that the social context in which the movie was produced, in other words, at a time that movies of this kind rose up to criticize a conservative ideology, contributed to the building of a character oppressed in his own space.